Peran Mediasi Kebijakan Dividen Pada Pengaruh Struktur Modal Terhadap Nilai Perusahaan - Elawati Dewi; Akhmadi Akhmadi; Wawan Ichwanudin (Sains: Jurnal Manajemen dan Bisnis, 2026)
This study examines the role of dividend policy in mediating the effect of capital structure on firm value. The population in this study was all 83 companies in the Basic Industry and Chemicals subsector listed on the Indonesia Stock Exchange for the 2015-2021 period. The sample consisted of 58 companies in the Basic Industry and Chemicals subsector listed on the IDX for the 2015-2021 period, determined using a purposive sampling technique. Data collection methods used library research and documentation research. Data analysis used STATA. The results showed that capital structure had a significant negative effect on firm value. Capital structure had a positive but insignificant effect on dividend policy. Dividend policy had a positive but insignificant effect on firm value. Dividend policy did not mediate the effect of capital structure on dividend policy.